Edukasi Ibu Hamil Resiko Tinggi Dan Pemberian Tablet Fe Dalam Rangka Mencegah Resiko Keluarga Stunting Di Dusun Iii Desa E Wonokerto - Siti Sofiah; Umayah , Meilany Rifda; Sugiarti, Sugiarti; Rossita, Taufianie (Jurnal Pakar Pengabdian Kesehatan, 2025)
High-risk pregnancy is a serious challenge in maternal health services, especially in rural areas with limited access to information and healthcare facilities. E Wonokerto Village, Tugumulyo Subdistrict, Musi Rawas Regency, has reported a relatively high prevalence of Resiko Tinggi based on data from the local health center. This study aims to analyze the situation of high-risk pregnant women, evaluate the effectiveness of community-based intervention programs, and formulate strategies to improve the quality of antenatal care services. Based on the report in 2024, there were 31 pregnant women recorded, with 7 classified as high-risk, while in the 2025 report, there were 10 pregnant women recorded, with 3 (36.5%) classified as high-risk. Using a descriptive qualitative method and a participatory approach, the study found that intensive education and social support play a crucial role in reducing the risk of Resiko Tinggi. Additionally, the research highlights that the lack of knowledge among pregnant women regarding danger signs of pregnancy and limited access to adequate healthcare facilities are the main barriers to managing Resiko Tinggi in this village. The community-based intervention program, involving health cadres and community leaders, was found to be effective in raising awareness about pregnancy risks and the importance of regular antenatal check-ups. The findings support the need for improved maternal healthcare services through a more holistic and community-empowerment-based approach. The study recommends enhanced training for local health workers as well as improving transportation access for pregnant women to reach adequate healthcare facilities.